2008
DOI: 10.1093/jpepsy/jsn119
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A Qualitative Analysis of Discussions about HIV in Families of Parents with HIV

Abstract: Discussions between youth and their parent with HIV and their siblings vary, highlighting the need for further research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…Similar to a study by Corona et al (2009), many of the women in this study reported their own experience of living with HIV shaped their conversations with their child, and some used themselves as an “example.” Contrary to previous findings (Corona et al, 2009), our findings suggest some mothers would not have discussed sexual topics/safer sex with their children had it not been for their experience with HIV illness. This pattern was also observed for parent-child discussions on tobacco use (but not alcohol use); parents who smoke cigarettes tended to communicate more with their children about smoking, specifically discussing rules and discipline pertaining to tobacco use (Ennett, Bauman, Foshee, Pemberton, & Hicks, 2001).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar to a study by Corona et al (2009), many of the women in this study reported their own experience of living with HIV shaped their conversations with their child, and some used themselves as an “example.” Contrary to previous findings (Corona et al, 2009), our findings suggest some mothers would not have discussed sexual topics/safer sex with their children had it not been for their experience with HIV illness. This pattern was also observed for parent-child discussions on tobacco use (but not alcohol use); parents who smoke cigarettes tended to communicate more with their children about smoking, specifically discussing rules and discipline pertaining to tobacco use (Ennett, Bauman, Foshee, Pemberton, & Hicks, 2001).…”
Section: Discussionsupporting
confidence: 59%
“…While there was some discomfort, the study also found that both parents and children expressed openness and comfort sharing information. Messages conveyed included: parents encouraging their children not to make the same mistakes they made; parents drawing on the their experience with HIV (e.g., the children observed their parent's hospitalizations and fluctuating health); and discussion about safer sex and how HIV is transmitted (Corona et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…To date, only one study has specifically evaluated the impact of maternal HIV serostatus on engagement by adolescents in HIV risk behaviors (Mellins, Brackis-Cott, Dolezal, & Meyer-Bahlburg, 2005). Only three (Corona et al, 2009; Marhefka et al, 2009; O’Sullivan et al, 2005) have examined parent-child communication within families where the parent is HIV infected. Because of the reported risk among this adolescent group for their own sexually acquired HIV infection, more information about this population is needed to better understand their HIV risk reduction needs.…”
Section: Limits Of Existing Literaturementioning
confidence: 99%
“…In families where the mother is HIV infected, far less is known about mother-daughter sexual risk communication. To date, only three studies have examined how discussions about HIV may differ in families with an HIV-positive parent (Corona et al, 2009; Marhefka, Mellins, Brackis-Cott, Dolezal, & Ehrhardt, 2009; O’Sullivan, Dolezal, Brackis-Cott, Traeger, & Mellins, 2005). This study sought to add to our understanding of how living with HIV impacts mother-daughter dyads, particularly, sexual risk communication.…”
mentioning
confidence: 99%
“…23,25 Although previous studies have queried HIV-infected parents on whether they discussed safer sex and HIV prevention with adolescents, 13,2630 the content 13,2630 and context of such talks, 27 their perceived conversational outcomes 27,30 and comfort level, 27,28 and what role their HIV status played in these discussions, 13,30 no study has focused on factors that encourage or prevent parents from broaching these important topics.…”
mentioning
confidence: 99%